Effectiveness of Transdermal Patch Compressed Red Ginger Ekstract (Zingiber Officinale Var.Rubrum) as Therapy Alternative to Flowness Breast Milk in Postpartum Mothers - Ladyvia, Fiyola; Hadisaputro, Suharyo; Suwondo, Ari (GLOBAL HEALTH SCIENCE GROUP, 2024)
Breast milk smoothness occurs because the blockage of venous and lymphatic flow increases, causing breast swelling, inhibiting milk flow, and pain in the breast and increasing body temperature, if not treated immediately there can be breast milk dams, mastitis and even breast infections. This causes pain, to reduce breast swelling non-pharmacologically can be done with the development of transdermal patch compress red ginger extract. The research purposes is a resulted in the development of a viable red ginger extract transdermal patch compress and proved its effectiveness as an alternative therapy for smooth breastfeeding in postpartum mothers. Produce and analyze its effectiveness as an alternative therapy for smooth breast milk in postpartum mothers. Method: This type of research is R&D, and quasi-experimental Pre-Posttest With Control Group Design. The sample amounted to 30 postpartum mothers divided into 2 intervention groups with the development of transdermal patches of red ginger extract and breastcare and a control group with breasrcare. The variables measured were breast milk volume, decreased swelling and breast tenderness. Consecutive sampling technique. Data collection using questionnaires and observations. Data analysis using univariate and bivariate using Wilcoxon and Mann Whitney. The development of transdermal red ginger extract patches is validated and feasible to be applied as an alternative therapy to smooth breast milk of puerperal mothers. Test results of effectiveness of increasing breast milk volume from 2,47 to 71,07 (p = 0.000), decreasing breast swelling from 3,45 to 1,32 (p = 0.000), breast pain from 2,91 to 0,14 (p = 0.001). The application of the development of Transdermal Extract Red Ginger Patch is feasible and effective as an alternative therapy against the smooth breastfeeding of puerperal mothers.